Iridium and Rhodium Complexes with the Hemilabile Ligand [2‐(1, 3‐Dioxolane‐2‐yl)phenyl]diphenylphosphane – Behaviour in Solution and Structural Characterization. Issue 7 (19th December 2012) - Barquín, Montserrat; Ciganda, Roberto; Garralda, María A.; Ibarlucea, Lourdes; Mendicute‐Fierro, Claudio; Rodríguez‐Diéguez, Antonio; Seco, José M.
Abstract: [MCl(L2 )]2 (M = Ir, L2 = 1, 5‐cyclooctadiene; M = Rh, L2 = norbornadiene) reacts with [2‐(1, 3‐dioxolane‐2‐yl)phenyl]diphenylphosphane (1 ) to afford [MCl(L2 )(P O)] (M = Ir, 2 ; M = Rh, 3 ), in which the ligand is P‐monodentate. Complex3 reacts with AgClO4 to give [Rh(Nbd)(PO)]ClO4 (4 ), in which the ligand is P, O‐bidentate. Complex2 is static at room temp., whereas3 and4 undergo intramolecular exchanges, which are fast at room temperature and slow at 223 K. The conformational changes in4 are still fast at 223 K. Complexes2 –4 react with CO to afford trans ‐[MCl(CO)(P O)2 ] (M = Ir, 5 ; M = Rh, 6 ) or trans ‐[Rh(CO)2 (P O)2 ]ClO4 (7 ). Cyclooctadiene complexes react with PPh2 ( o ‐C6 H4 CHO) to afford [MClH(PPh2 ( o ‐C6 H4 CO))(PO] (M = Ir, 8 ; M = Rh, 9 ), in which1 is chelating. Complex8 contains a single diastereomer, is static in the 303–213 K range and reacts with CO to form [IrClH(PPh2 ( o ‐C6 H4 CO))(P O)(CO)] (10 ). Complex9 contains two diastereomers9a /9b in a 95:5 ratio that undergo interconversion, which is slow at low temperature, and reacts with CO to undergo reductive elimination of aldehyde, cleavage of the Rh–O bond and scrambling of phosphanes. A mixture of trans ‐[RhCl(CO)(κ 1 ‐PPh2 ( o ‐C6 H4 CHO))(P O)] (11 ), 6 and trans ‐[RhCl(CO)(κ 1 ‐PPh2 ( o ‐C6 H4 CHO))2 ] is formed. Bubbling of nitrogen transforms11 back into9 . Compound2 reacts with hydrogen to give the fluxional [IrCl(H)2 (P O)(PO)] (12 ) with trans P atoms and cis H atoms, which attains coalescence at 203 K. Complex12 reacts with mono‐ or bidentate ligands to afford static [IrCl(H)2 (P O)2 L] (L = CO, 13 ; py, 14 ; n PrNH2, 15 ) or [Ir(H)2 (P O)2 (en)]BPh4 (16, en = ethylenediamine). Abstraction of halide from12 affords [Ir(H)2 (PO)2 ]BPh4 (17 ), which is fluxional owing to interconversion between only two of the possible four diastereomers, for which Δ H ‡ = 54.7 ± 0.7 kJ mol –1 and Δ S ‡ = 4.7 ± 0.2 J K –1 mol –1 . The X‐ray structures of8, 15 and16 are also reported. Abstract : [2‐(1, 3‐Dioxolane‐2‐yl)phenyl]diphenylphosphane (1 ) coordinates to M I preferably as a κ 1 ‐P ligand. M III may afford κ 2 ‐P, O coordination in dynamic diastereomers such asA orB .A contains a single diastereomer if M = Ir or two diastereomers in a 95:5 ratio if M = Rh.B contains a mixture of only two diastereomers.